Топологічна класифікація дробово-лінійних перетворень - Будницька, T.В. (Інститут математики НАН України, 2009)
The linear fractional transformations from C to C are investigated. Necessary and sufficient conditions for a topological conjugacy of such trans-formations are obtained.